1367 RECOGNITION AND MANAGEMENT OF ACUTE FUNCTIONAL DECLINE: A QUALITATIVE INTERVIEW STUDY WITH UK CARE HOME STAFF. (16th January 2023) - Moore, A; Glogowska, M; Lasserson, D; Hayward, G
Abstract: Introduction: Older people living in care homes sometimes experience episodes of acute functional decline. These represent a diagnostic challenge to healthcare professionals and can result in antibiotic prescriptions or hospital admissions, though this may not always the most appropriate management strategy. We aimed to understand how episodes of acute functional decline are recognised, managed and escalated by care home staff in the UK. Method: This was a qualitative interview study with UK care home staff, including managers, nurses and carers. Participants were recruited through advertisements circulated via email, social media and word of mouth. Semi-structured interviews were conducted over the phone between January 2021 and April 2022. Thematic analysis was facilitated by NVivo software. Results: 25 care home staff were interviewed. Participants described feeling confident in recognising when residents were less well than usual, especially if they knew them well. However, they sometimes felt it was difficult to differentiate between an 'off day' and something more significant. Most participants talked about clear early communication amongst the team to flag a resident of concern. Initial management steps in the care home included checking clinical observations and doing a urine dipstick. Many participants talked about considering the underlying cause for deterioration. Some participants felt comfortable monitoring residents for a few days themselves or trying a simple intervention. Others preferred escalating directly to outside clinical support. Triggers for escalation included perceived severity of illness, gut feeling or failure to respond to initial supportive management. Conclusions: These results highlight the skill base of care home staff. However, it has also helped to identify areas for additional support and training including the use and interpretation of the urine dipstick. The findings of this study are being used to inform the design of a feasibility prospective cohort study of UK care home residents.